THE DEVELOPMENT OF THE SCIENCE PROGRAM IN CHILDHOOD EDUCATION IN THE GREAT NECK PUBLIC SCHOOLS. - Ashley, Tracy (Science Education, 1955)
The article focuses on the development of the science program in childhood education in the Great Neck public schools in New York. According to the article, prior to 1948 most of the science experiences of the children in elementary schools came as a result of a special science teacher who taught science on a departmentalized basis in the fifth and sixth grades. In 1946-1947, a committee of lay people, the administration and professional staff conducted a "Survey of the Great Neck Public Schools. One of the recommendations of the survey was that the science specialists in the elementary schools work as consultants and resource people to the classroom teacher. This marks the beginning of the development of the science program in the schools in Great Neck.